Direct Observation of Subrelativistic Electron Precipitation Potentially Driven by EMIC Waves. Issue 22 (25th November 2019) - Capannolo, L.; Li, W.; Ma, Q.; Chen, L.; Shen, X.‐C.; Spence, H. E.; Sample, J.; Johnson, A.; Shumko, M.; Klumpar, D. M.; Redmon, R. J.
Abstract: Electromagnetic ion cyclotron (EMIC) waves are known to typically cause electron losses into Earth's upper atmosphere at > 1 MeV, while the minimum energy of electrons subject to efficient EMIC‐driven precipitation loss is unresolved. This letter reports electron precipitation from subrelativistic energies of 250 keV up to 1 MeV observed by the Focused Investigations of Relativistic Electron Burst Intensity, Range and Dynamics (FIREBIRD‐II) CubeSats, while two Polar Operational Environmental Satellites (POES) observed proton precipitation nearby. Van Allen Probe A detected EMIC waves ( 0.7–2.0 nT) over the similar L shell extent of electron precipitation observed by FIREBIRD‐II, albeit with a 1.6 magnetic local time (MLT) difference. Although plasmaspheric hiss and magnetosonic waves were also observed, quasi‐linear calculations indicate that EMIC waves were the most efficient in driving the electron precipitation. Quasi‐linear theory predicts efficient precipitation at >0.8–1 MeV (due to H‐band EMIC waves), suggesting that other mechanisms are required to explain the observed subrelativistic electron precipitation. Plain Language Summary: Plasma waves in the Earth's magnetosphere can alter the trajectory of particles traveling along geomagnetic field lines. Specifically, electromagnetic ion cyclotron (EMIC) waves can interact with both electrons and protons and cause them to fall into the upper atmosphere of Earth. From past studies and theories, it is known that EMIC waves drive precipitation of ultrarelativistic (> MeV) electrons and tens to hundreds of keV protons. Such electron precipitation can lead to atmospheric changes and potentially aid ozone depletion. In this work, we show a direct observation of electron precipitation from 250 keV up to 1 MeV, potentially driven by EMIC waves using multipoint measurements primarily from a CubeSat mission (FIREBIRD‐II) and Van Allen Probes. Quasi‐linear calculations indicate that EMIC waves are efficient in driving the electron precipitation at >0.8–1 MeV, but other mechanisms are needed to explain the observed electron precipitation down to 250 keV. Our study also highlights the capabilities of FIREBIRD‐II studying not only microbursts, but also other precipitation patterns (e.g., driven by EMIC waves). Key Points: Strong EMIC waves were observed by Van Allen Probe A in association with phase space density dips over the similar L shell extent FIREBIRD‐II observed electron precipitation from 250 keV up to 1 MeV over the similar L shell extent of EMIC waves but at a later MLT Quasi‐linear theory predicts efficient precipitation at > 0.8–1 MeV but requires other mechanisms to explain the subrelativistic one